Understanding Pakistani parents' experience of having a child with special educational needs and disability (SEND) in England. Issue 5 (19th October 2020) - Akbar, Sarwat; Woods, Kevin
ABSTRACT: As a response to calls for social justice and promotion of children's rights across increasingly diverse communities, the need for 'culturally competent' services to children, families and schools has been identified. The aim of the paper is to explore, for parents of Pakistani minority ethnic heritage in England, the role of culture and religion in shaping their understanding of disability and their experience of special educational needs and disability (SEND) services. In-depth interviews and thematic analysis were used with 10 Pakistani heritage caregivers in England who have a child with a developmental disability and a statutory identification of need for SEND (Educational, Health and Care Plan). For these parents, hidden disabilities are more difficult to understand, explain and seek services for; stigma is a major source of stress, leading to strained marital relationships, whilst faith acts as a protective factor. Within special education processes, language, perceived power differentials and mistrust are barriers to accessing appropriate services. Educational psychology services for children and families will need to find ways of adapting to engage members of diverse communities in order to protect and promote the rights of children with disabilities. The following was identified as a limitation: recruitment through schools may have identified only those parents already engaged with professionals.